Restaurant Business Development Strategy in Pantai Panjang - Sahrul Arleza; Romi Gunawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to examine and determine business development strategies in restaurants in Pantai Panjang. This research uses descriptive quantitative and qualitative methods. Qualitative analysis is used to determine the external and internal factors of restaurant businesses. Quantitative descriptive analysis is used in the IFE, EFE and SWOT matrices. The population used in this study is a restaurant business on Panjang Beach Tourism Road in Bengkulu City. Based on the research results, it can be concluded that based on the analysis that has been carried out in Figure 1 SWOT matrix analysis, the restaurant business development strategy in Beach is in quadrant II, namely supporting a verified strategy which uses strength to overcome existing threats, so the ST strategy: Using strength to overcome threats.